The Influence of Local Government Size and Economic Growth on Local Government Financial Performance - Nasirwan, Nasirwan; Ginting, Aisah Br; Manalu, Christina; Sinaga, Desy Amelia (Economic: Journal Economic and Business, 2024)
Performance measurement is an important element in assessing the effectiveness of policy implementation, including financial regulations at the local government level. By measuring financial performance, we can obtain valuable feedback regarding the suitability and accuracy of implementing these regulations. The aim of this research is to analyze the influence of local government size and economic growth on local government financial performance. In this study, the sample used in this research was a purposive sampling sample, with the population of Regional Governments and Regency/City Regional People's Representative Councils (DPRD) in Indonesia in 2018.